(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pune city has a very high density of private vehicles. Core (Peths) Pune has limited road capacity and high travel demand creating a traffic congestion problem. This reduce the use of public transport leading to traffic problems. To address all cascading traffic issues, a study for congestion charging as a possible solution for the Pune city core area has been proposed